Profitabilitas, Kepemilikan Publik, Kebijakan Dividen, dan Praktik Income Smoothing - Paras Masari Teja Nirmala, Ni Putu; Latrini, Made Yenni (E-Jurnal Akuntansi; Vol 34 No 7 (2024), 2024)
This study attempts to show how profitability, public ownership, and dividend policy affect income smoothing practices. The scope of this study is banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. The research sample of 62 observations was the result of selection from the purposive sampling technique. Multiple linear regression analysis method were applied to analyze the research data. Based on the results of the analysis, empirical evidence was obtained that income smoothing practices were negatively influenced by profitability and income smoothing practices were positively influenced by public ownership. Meanwhile, dividend policy does not show a significant influence on income smoothing practices. Keywords: Profitability; Public Ownership; Dividend Policy; Income Smoothing Practice